Novel nicotinic hydrazone derivatives as multitarget carbonic anhydrase and acetylcholinesterase inhibitors with anticancer potential: synthesis, biological evaluation and molecular docking studies - Aslan, Osman Nuri; Korkmaz, Isil Nihan; Kaci, Fatma Necmiye; Kalin, Pinar; Kalay, Erbay; Guller, Ugur; Kalin, Ramazan (Taylor & Francis Ltd, 2026)
AimsThis study aims to design and synthesize novel nicotinic hydrazone derivatives and evaluate their multitarget biological activities, including enzyme inhibition and anticancer potential.Materials and methodsThe target compounds were synthesized via condensation of nicotinic hydrazide with various aldehydes, including Mannich base and acyl-substituted derivatives. Structural characterization was performed using 1H NMR, 13C NMR, FT-IR, and HRMS, and purity was confirmed by HPLC. Enzyme inhibition (hCA I, hCA II, and eeAChE), molecular docking, in silico ADME analysis, and cytotoxic activity against A549, HeLa, HepG2, and SH-SY5Y cell lines were evaluated.ResultsSeveral compounds exhibited potent enzyme inhibition in the nanomolar range. Compounds 2c, 2a, and 2b showed the strongest inhibition against hCA I, hCA II, and eeAChE, respectively (Ki = 9.05-16.93 nM). Docking studies revealed favorable binding interactions, with compound 2f showing the highest overall affinity. All compounds complied with Lipinski's rule of five. Cytotoxicity studies demonstrated strong activity, particularly for compounds 2a, 2d, and 2e.ConclusionsNicotinic hydrazone derivatives represent promising multitarget scaffolds with significant enzyme inhibitory and anticancer potential, warranting further investigation.
Keywords: Nicotinic Hydrazone; Anticancer Activity; Enzyme Inhibition; Antibacterial Activity; Molecular Docking